Dialogical elements in Harris, Dewey, Cutter, Otlet, Kaiser, and Ranganathan: Theoretical convergences in the history of Knowledge Organization - Sales, Rodrigo de; Martínez-Ávila, Daniel; Guimarães, José Augusto (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2019)
In this paper, we study the theoretical intersections and dialogues between some foundational authors on classification and indexing of the nineteenth and twentieth centuries that helped developing the theoretical-methodological framework of knowledge organization. More specifically, we highlight and analyze the theoretical convergences of Harris, Dewey, Cutter, Otlet, Kaiser, and Ranganathan as they can provide a clearer picture of the historical and theoretical contributions to the epistemological foundations of knowledge organization. Our methodology follows a critical-descriptive approach to the analysis of the main contributions of the authors and the critical reflections of some specialists and biographers. We continue with a discussion of the links between bibliographic classifications and knowledge organization drawing on the ideas of Bliss; then, we divide our historical narrative between the theoretical contributions during the nineteenth-century (Harris, Dewey, and Cutter) and the twentieth century (Otlet, Kaiser, and Ranganathan); and finally, we present a discussion of the history of knowledge organization from the point of view of the theoretical and methodological development of classification and indexing at the turn of the nineteenth century to the twentieth century. We conclude with some remarks on their main contributions to the development of the knowledge organization field. Keywords: Classification. Indexing. Knowledge Organization Link: http://www.scielo.br/scielo.php?script=sci_arttext&pid=S0103-37862018000300348&lng=pt&nrm=iso&tlng=en